2020
DOI: 10.1155/2020/3174674
|View full text |Cite
|
Sign up to set email alerts
|

Bellini Duct Carcinoma Misdiagnosed with Urothelial Papillary Carcinoma

Abstract: Background. Collecting (Bellini) duct carcinoma (CDC) or Bellini duct carcinoma (BDC) is a rare subtype of kidney tumors, accounting for less than 3% and known to have the worst prognosis. It is known to have multiple clinical presentations; this is why it can be easily misdiagnosed. The aim of this article is to present a case of CDC that was initially misdiagnosed with urothelial papillary carcinoma (UPC) in a 41-year-old male. Case Presentation. Our patient presented with a left flank pain evolving for one … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 9 publications
0
2
0
Order By: Relevance
“…Firstly, the established models were based on a secondary analysis on a publicly available database. Previous studies suggested that CDRCC is difficult to be differentiated from other histologic subtypes like medullary RCC and urothelial papillary carcinoma [ 31 , 32 ]. Thus, the lack of centralized pathology review may cause misclassification in the study cohort, which limits the quality of the data.…”
Section: Discussionmentioning
confidence: 99%
“…Firstly, the established models were based on a secondary analysis on a publicly available database. Previous studies suggested that CDRCC is difficult to be differentiated from other histologic subtypes like medullary RCC and urothelial papillary carcinoma [ 31 , 32 ]. Thus, the lack of centralized pathology review may cause misclassification in the study cohort, which limits the quality of the data.…”
Section: Discussionmentioning
confidence: 99%
“…In 2 patients with CRCC and 10 patients with CCDC had retroperitoneal lymph node or distant metastasis ( P < 0.0001). Hence the differential biological behavior of the tumors may also provide useful diagnostic information [ 29 ].…”
Section: Discussionmentioning
confidence: 99%